Online Job Portal with Psychometric Test - Gurtej Singh, Sarjit Singh (Universiti Malaysia Sarawak, (UNIMAS), 2023)
The process of finding and hiring qualified individuals for a job is known as recruitment. The use of an online system that includes a psychometric test is a type of recruitment system that assesses potential job seekers. This report will focus on developing an online job portal that incorporates a psychometric test. The system will allow job seekers to find their ideal job while also allowing recruitment managers to find the best candidates for the position. Recruitment managers will be able to select a set of psychometric tests for job seekers to take before applying for a job. The main purpose of the psychometric test is to provide recruitment managers with more information about the job seeker skills and behavior. The outcome of this project will be a Online Job Portal with Psychometric Testing that helps recruitment managers identify potential candidates. The system will be evaluated, and improvements will be documented and analyzed.